Konstitusi, Negara Hukum dan Hak Asasi Manusia: Menegakkan Konstitusi Menuju Perlindungan HAM di Negara Hukum Indonesia - Udiyo Basuki (IN RIGHT: Jurnal Agama dan Hak Azazi Manusia, 2026)
Constitution, rule of law, and human rights are three interrelated pillars in the administration of a democratic state. The constitution serves as the supreme law that limits governmental power while guaranteeing the protection of fundamental rights. This article aims to analyze the dynamics of human rights regulation within the Indonesian Constitution, particularly the 1945 Constitution of the Republic of Indonesia, and to examine contemporary challenges in human rights protection and enforcement along with their possible solutions. This study employs a normative juridical method, utilizing statutory and conceptual approaches, supported by library research. The findings reveal that the regulation of human rights in the 1945 Constitution has undergone significant development, evolving from limited provisions in the original constitutional text to comprehensive constitutional guarantees through Chapter XA, Articles 28A–28J, following the constitutional amendments. These developments reflect Indonesia’s commitment as a rule of law state to respect, protect, and fulfill human rights. Nevertheless, the implementation of these constitutional guarantees continues to face several challenges, including unresolved cases of past gross human rights violations, weak law enforcement and abuse of power, persistent intolerance and discrimination, and inadequate protection of vulnerable and marginalized groups. Therefore, strategic measures are required, including the resolution of human rights violations, judicial reform, enhancement of human rights literacy, and stronger protection mechanisms for vulnerable groups to realize a just rule-of-law state that upholds human dignity.Konstitusi, negara hukum, dan hak asasi manusia (HAM) merupakan tiga konsep yang memiliki hubungan erat dalam penyelenggaraan negara demokratis. Konstitusi berfungsi sebagai hukum tertinggi yang membatasi kekuasaan negara sekaligus menjamin perlindungan hak-hak dasar warga negara. Artikel ini bertujuan untuk menganalisis dinamika pengaturan HAM dalam konstitusi Indonesia, khususnya Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, serta mengkaji berbagai problematika aktual dalam perlindungan dan penegakan HAM beserta alternatif solusinya. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan konseptual yang didukung oleh studi kepustakaan. Hasil penelitian menunjukkan bahwa pengaturan HAM dalam UUD 1945 mengalami perkembangan signifikan, mulai dari pengaturan yang terbatas pada naskah awal UUD 1945 hingga penguatan jaminan konstitusional melalui Bab XA Pasal 28A sampai dengan Pasal 28J pasca-amandemen. Perubahan tersebut mencerminkan komitmen negara hukum Indonesia dalam menjamin penghormatan, perlindungan, dan pemenuhan HAM. Namun demikian, implementasinya masih menghadapi berbagai tantangan, antara lain belum tuntasnya penyelesaian pelanggaran HAM berat masa lalu, lemahnya penegakan hukum dan penyalahgunaan kekuasaan, maraknya intoleransi dan diskriminasi, serta belum optimalnya perlindungan terhadap kelompok rentan dan marginal. Oleh karena itu, diperlukan langkah strategis berupa penyelesaian kasus HAM secara adil, reformasi sistem peradilan, peningkatan literasi HAM, dan penguatan perlindungan bagi kelompok rentan guna mewujudkan negara hukum yang berkeadilan dan menghormati martabat manusia.